2014
DOI: 10.1186/cc13813
|View full text |Cite
|
Sign up to set email alerts
|

Open lung approach with low tidal volume mechanical ventilation attenuates lung injury in rats with massive brain damage

Abstract: IntroductionThe ideal ventilation strategy for patients with massive brain damage requires better elucidation. We hypothesized that in the presence of massive brain injury, a ventilation strategy using low (6 milliliters per kilogram ideal body weight) tidal volume (VT) ventilation with open lung positive end-expiratory pressure (LVT/OLPEEP) set according to the minimal static elastance of the respiratory system, attenuates the impact of massive brain damage on gas-exchange, respiratory mechanics, lung histolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 48 publications
(66 reference statements)
1
14
0
Order By: Relevance
“…Previous guidelines recommended the use of liberal tidal volumes [10-15 mL/ kg of predicted body weight (PBW)] [27] with positive end expiratory pressure (PEEP) of at least 5 cmH 2 O to treat NPE. However, ventilator-induced lung injury is common in organ donors [28], and recent experimental evidence shows that protective ventilation attenuates the severity of lung injury [29]. A protective ventilator strategy bundle (using 6-8 mL/kg of PBW, PEEP equal to 8-10 cmH 2 O, a closed circuit for tracheal suction, alveolar recruitment manoeuvres after any disconnection, [8], an approach similar to the management of acute lung injury patients [31,32].…”
Section: Respiratory Managementmentioning
confidence: 99%
“…Previous guidelines recommended the use of liberal tidal volumes [10-15 mL/ kg of predicted body weight (PBW)] [27] with positive end expiratory pressure (PEEP) of at least 5 cmH 2 O to treat NPE. However, ventilator-induced lung injury is common in organ donors [28], and recent experimental evidence shows that protective ventilation attenuates the severity of lung injury [29]. A protective ventilator strategy bundle (using 6-8 mL/kg of PBW, PEEP equal to 8-10 cmH 2 O, a closed circuit for tracheal suction, alveolar recruitment manoeuvres after any disconnection, [8], an approach similar to the management of acute lung injury patients [31,32].…”
Section: Respiratory Managementmentioning
confidence: 99%
“…We first performed a systematic search of NIH GEO and ArrayExpress for studies of either type. There were 21 animal lung tissue datasets (19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38) with diverse lung injury mechanisms, including ventilator-induced injury (n = 14), ozone (n = 3), intratracheal LPS (n = 3), and a hemorrhagic trauma model (n = 1) (total controls = 83, cases = 141; Table 1). No human ALI whole-lung samples were available, so we used three human experimental datasets (39-41) that studied LPS or ozone exposure via BAL (total microarrays: controls = 107, cases = 110; Table 2).…”
Section: Multicohort Gene Expression Analysesmentioning
confidence: 99%
“…A consensus has been formed that it is also suitable for patients with healthy lungs in operating room [9,10]. An animal experiment showed that small VT ventilation could more effectively promote the oxygenation of rats with brain injury than large VT ventilation [11]. Furthermore, large VT ventilation in TBI patients might be associated with the occurrence of ARDS, and its incidence increased to some extent with the VT [12].…”
Section: Discussionmentioning
confidence: 99%